Urinary Catheter Colonization by Multidrug-Resistant Cedecea neteri in Patient with Benign Prostatic Hyperplasia. (11th July 2018) - Ginn, Peter S.; Tart, Serina B.; Sharkady, Stephen M.; Thompson, Dorothea K.
Abstract : Cedecea neteri, a member of the Enterobacteriaceae family, has only been identified as a human pathogen in a few previous clinical cases, thus complicating assessment of this organism's pathogenicity and medical relevance. Documented infections attributed to C. neteri primarily involved bacteremia in severely immunocompromised patients. We report a rare case of urinary catheter colonization by a multidrug-resistant C. neteri strain in a patient of advanced age with benign prostatic hyperplasia and other chronic comorbidities. This C. neteri isolate was resistant or intermediate to second-generation cephalosporins, penicillins, and certain β -lactamase inhibitor/ β -lactam combinations. Analysis of whole genome sequence information for a representative C. neteri strain indicated the presence of multiple open reading frames with sequence similarity to β -lactamases, including a chromosome-encoded AmpC β -lactamase and metallo- β -lactamases, consistent with the resistance phenotype of this bacterium. The presence of an AmpR homolog suggests that the C. neteri ampC may be inducible in response to β -lactam exposure. Molecular insights into antibiotic resistance traits of this emerging opportunistic pathogen will be important for administering adequate antibiotic treatment to ensure favorable patient outcomes.